Motivation and attitudes towards English language learning in post-revolution Tunisia: A study across educational levels - Salah, Rania; Parapatics, Andrea (Universitas Syiah Kuala, 2025)
The present study explores two primary social psychological factorsmotivation and attitudestowards learning the English language across various educational levels following the 2011 revolution in Tunisia. Utilizing a mixed-method research approach, this study combined quantitative and qualitative data collection methods to gain comprehensive insights. An arbitrary sample of 170 students, from primary to secondary education and university levels, was surveyed using the Attitude/Motivation Test Battery. Additionally, semi-structured interviews were conducted with 9 students and 3 directors from three educational institutions. The study encompassed six key domains: (1) attitudes regarding English language learning, (2) motivation, (3) integrative motivation, (4) instrumental motivation, (5) parental involvement, and (6) attitudes towards language policies. The results indicate that students exhibited positive attitudes and high motivation toward learning English. Furthermore, the data revealed a positive orientation toward learning the English language in terms of integrative and instrumental motivation. Notably, instrumental motives were identified as the primary basis for students motivation to learn English, slightly surpassing their integrative motivation. Moreover, a significant and positive correlation between attitude and motivation was observed. Conversely, the findings unveiled that all interviewees perceived educational policies as detrimental to English language learning. Their collective feedback underscored persistent challenges associated with English language education in school environments and society. Ultimately, all participants, either directly or indirectly, advocated for a heightened emphasis on the importance of English and called for a revision of language policies.